2023
DOI: 10.3389/fpls.2023.1133095
|View full text |Cite
|
Sign up to set email alerts
|

Crop rotation with Meloidogyne-resistant germplasm is useful to manage and revert the (a)virulent populations of Mi1.2 gene and reduce yield losses

Abstract: A rotation sequence of ungrafted and grafted tomato-melon-pepper-watermelon on resistant rootstocks ‘Brigeor’, Cucumis metuliferus, ‘Oscos’ and Citrullus amarus, respectively, was carried out in a plastic greenhouse, ending with a susceptible or resistant tomato crop. The rotation was conducted in plots infested by an avirulent (Avi) or a partially virulent (Vi) Meloidogyne incognita population to the Mi1.2 gene. At the beginning of the study, the reproduction index (RI, relative reproduction in the resistant … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 55 publications
(85 reference statements)
0
10
0
Order By: Relevance
“…In short, this study contributes to provide information on lettuce and bean germplasm able to reduce M. incognita and M. javanica to be included in a crop rotation sequence as an alternative to chemical control. Moreover, the inclusion of different resistance genes in crop rotation sequences can contribute to the durability of each single resistance gene despite having been previously selected for their virulence to a specific resistance gene [ 12 , 38 ]. Furthermore, if selection for virulence of a given specific resistance gene did occur, it would not compromise other resistance genes [ 39 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In short, this study contributes to provide information on lettuce and bean germplasm able to reduce M. incognita and M. javanica to be included in a crop rotation sequence as an alternative to chemical control. Moreover, the inclusion of different resistance genes in crop rotation sequences can contribute to the durability of each single resistance gene despite having been previously selected for their virulence to a specific resistance gene [ 12 , 38 ]. Furthermore, if selection for virulence of a given specific resistance gene did occur, it would not compromise other resistance genes [ 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…Also, the repeated cultivation of resistant tomato cultivars carrying the Mi 1.2 gene may allow for the development of virulent RKN populations or species [ 9 , 10 , 11 ]. The effectiveness and durability of a given resistance source can be maximized if it is included in rotation sequences with plants carrying different resistance genes and/or with non- or poor hosts [ 12 ]. The host status of a given plant to a given nematode species is defined by the relationship between the nematode densities at the end of the crop or experiment ( Pf ) and the nematode densities at the beginning of the crop or experiment ( Pi ) [ 13 , 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, recently published greenhouse tests demonstrated that grafting may alleviate the problems of these pathotypes. New rotation sequences of grafted tomato-melon-pepper-watermelon on resistant rootstocks could revert the virulent Meloidogyne incognita populations on the Mi1.2 gene and consequently minimize yield losses compared to ungrafted plants [ 37 ]. Using resistant rootstocks, both intra- and interspecies grafting can provide safe and effective alternatives to choose and apply desirable PPN resistance trait in cultivated vegetables, whether in open-field or protected conditions.…”
Section: Proper Gene Pools and Scales Used To Determine Host Suscepti...mentioning
confidence: 99%
“…A better grasp of the nature of PPN–host interactions that regulate plant susceptibility/resistance can boost the discovery and use of PPN-resistant genes. Also, expansion of metagenomic tools and artificial intelligence for emerging PPN control plans will supply stakeholders with swifter, more accurate PPN identification and decision tools by properly revealing the food web in the plant rhizosphere and the exact mechanisms underlying PPN-suppressive soils [ 13 , 25 , 37 , 39 , 52 ].…”
Section: Bridging the Gap Between Current And Novel Strategies For Pp...mentioning
confidence: 99%
“…), with a worldwide distribution and host range of more than 3000 plant species [1][2][3]. RKNs can cause yield losses of 15-85% in vegetables, depending on the plant species and population density [1,4]. The infective second-stage juveniles (J2s) of RKNs hatch from eggs and penetrate the roots of host plants.…”
Section: Introductionmentioning
confidence: 99%